2011
DOI: 10.3109/03009742.2011.588400
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in diffuse cutaneous systemic scleroderma

Abstract: Patients with dcSSc have a high prevalence of sensorineural audiometric hearing impairment and otological complaints, suggesting that the cochlea is an additional target organ in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Monteiro et al, [6] in a study of twenty six patients revealed that patients with diffuse cutaneous systemic sclerosis have a high prevalence of sensorineural hearing impairment and otological complaints. The blood labyrinth barrier is analogous to the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Monteiro et al, [6] in a study of twenty six patients revealed that patients with diffuse cutaneous systemic sclerosis have a high prevalence of sensorineural hearing impairment and otological complaints. The blood labyrinth barrier is analogous to the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the existence of inner ear involvement in SSc patients, probably as a result of vascular damage, considering that the cochlea is highly sensitive to these changes. Blood changes and hypoxia in the cochlea resulting from SSc culminate with death of the ciliated cells (cochlear sensory structure), which is clinically expressed as hypoacusis and tinnitus (3)(4)(5)(6)(7)(8) . This mechanism of hypoxia in SSc is associated with activation of the endothelial cells by unknown factors, which promotes chronic endothelial injury with platelet adhesion and activation of the fibrinolytic system, thus generating increased vascular permeability and leukocyte adhesion to blood vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of bilateral SNHL among SSc patients ranges from 20% to 69%, while a conductive component contributes to the hearing loss in 3-11% of them [13,16,17]. Hearing loss and vestibular derangement were reported in SSc patients with an established diagnosis and not as the presenting symptom of the disease.…”
Section: Editorialmentioning
confidence: 99%
“…Ear involvement is frequent in SSc [13] and has been described in lcSSc [16] and dcSSc [17], where hearing loss and vestibulopathy coexist with other disease manifestations. The impairment of multiple vestibular endorgans points to peripheral vestibulopathy of ischemic origin or an intra-labyrinthine autoimmune process [16,18].…”
Section: Editorialmentioning
confidence: 99%